The decentralisation-centralisation dilemma: recruitment and distribution of health workers in remote districts of Tanzania - Songstad Nils; Munga Michael A; Blystad Astrid; Mæstad Ottar (BMC, 2009)
Abstract Background The implementation of decentralisation reforms in the health sector of Tanzania started in the 1980s. These reforms were intended to relinquish substantial powers and resources to districts to improve the development of the health sector. Little is known about the impact of decentralisation on recruitment and distribution of health workers at the district level. Reported difficulties in recruiting health workers to remote districts led the Government of Tanzania to partly re-instate central recruitment of health workers in 2006. The effects of this policy change are not yet documented. This study highlights the experiences and challenges associated with decentralisation and the partial re-centralisation in relation to the recruitment and distribution of health workers. Methods An exploratory qualitative study was conducted among informants recruited from five underserved, remote districts of mainland Tanzania. Additional informants were recruited from the central government, the NGO sector, international organisations and academia. A comparison of decentralised and the reinstated centralised systems was carried out in order to draw lessons necessary for improving recruitment, distribution and retention of health workers. Results The study has shown that recruitment of health workers under a decentralised arrangement has not only been characterised by complex bureaucratic procedures, but by severe delays and sometimes failure to get the required health workers. The study also revealed that recruitment of highly skilled health workers under decentralised arrangements may be both very difficult and expensive. Decentralised recruitment was perceived to be more effective in improving retention of the lower cadre health workers within the districts. In contrast, the centralised arrangement was perceived to be more effective both in recruiting qualified staff and balancing their distribution across districts, but poor in ensuring the retention of employees. Conclusion A combination of centralised and decentralised recruitment represents a promising hybrid form of health sector organisation in managing human resources by bringing the benefits of two worlds together. In order to ensure that the potential benefits of the two approaches are effectively integrated, careful balancing defining the local-central relationships in the management of human resources needs to be worked out.